Reliability and Validity Study of the Turkish Version of Child and Adolescent Social Support Scale for Healthy Behaviors - Sevil Albayrak; Biriz Çakır; Fatma Nişancı Kılınç; Özge Vergili; Yurdagül Erdem (Elsevier, 2018)
Purpose: The purpose of this study is to investigate adaptation, validity, and reliability of the Turkish version of the Child and Adolescent Social Support Scale for Healthy Behaviors (CASSS-HB). Methods: The CASSS-HB was translated using translation and back-translation. This was a methodological study conducted with 860 students (11-14 years old). Content and construct validity were assessed to test the validity of the CASSS-HB. Exploratory and confirmatory factor analysis of the scale was performed and the reliability of the scale over time (the test-retest method) was examined. Results: Psychometric analyses of the Turkish version of the CASSS-HB indicate high reliability and good content and construct validity. Conclusions: It can be seen that the items comprising the scale appear to be acceptably capable of measuring the variable of social support in terms of healthy behavior in children and adolescents. Healthcare professionals can thus use the scale for determining the degree of social support students of the ages 11-14 receive in terms of developing healthy behavior. Keywords: adolescent health, behavior, psychosocial support systems, reproducibility of results